Spatial Neglect Hinders Success of Inpatient Rehabilitation in Individuals With Traumatic Brain Injury: A Retrospective Study. (June 2016) - Chen, Peii; Ward, Irene; Khan, Ummais; Liu, Yan; Hreha, Kimberly
Background . Current knowledge about spatial neglect and its impact on rehabilitation mostly originates from stroke studies. Objective . To examine the impact of spatial neglect on rehabilitation outcome in individuals with traumatic brain injury (TBI). Methods . The retrospective study included 156 consecutive patients with TBI (73 women; median age = 69.5 years; interquartile range = 50-81 years) at an inpatient rehabilitation facility (IRF). We examined whether the presence of spatial neglect affected the Functional Independence Measure (FIM) scores, length of stay, or discharge disposition. Based on the available medical records, we also explored whether spatial neglect was associated with tactile sensation or muscle strength asymmetry in the extremities and whether specific brain injuries or lesions predicted spatial neglect. Results . In all, 30.1% (47 of 156) of the sample had spatial neglect. Sex, age, severity of TBI, or time postinjury did not differ between patients with and without spatial neglect. In comparison to patients without spatial neglect, patients with the disorder stayed in IRF 5 days longer, had lower FIM scores at discharge, improved slower in both Cognitive and Motor FIM scores, and might have less likelihood of return home. In addition, left-sided neglect was associated with asymmetric strength in the lower extremities, specifically left weaker than the right. Finally, brain injury–induced mass effect predicted left-sided neglect. Conclusions . Spatial neglect is common following TBI, impedes rehabilitation progress in both motor and cognitive domains, and prolongs length of stay. Future research is needed for linking specific traumatic injuries and lesioned networks to spatial neglect and related impairment.